The effect of hepatic regeneration on the expression of the glutathione S-transferases. - Lee, S J (1993)
The effect of hepatic regeneration on expression of four glutathione S-transferase (GST) subunits (Ya, Yc, Yb1, Yb2) was examined in rats following partial hepatectomy (PH). mRNA levels of the Ya and Yc subunits (Alpha class) decreased and were 13% and 42% of levels in sham-operated animals respectively 12 h after surgery. mRNA levels for the Yb1 subunit (Mu class) also decreased but were not maximally reduced until 24 h after PH (22% of sham-treated level). mRNA levels of the Yb2 subunit were affected little by PH. Changes in levels of mRNA appeared to reflect a decrease in both transcriptional activity and mRNA stability. The decrease in mRNA levels was associated with a fall in enzymic activity and in protein levels of Alpha-class GSTs. Within 48 h of surgery, levels of mRNA, protein enzymic activity and transcriptional activity had all fully recovered. GSH levels also decreased in the first 6 h after PH. However, 24 h after surgery GSH levels in animals having undergone PH exceeded those in sham-treated animals by 2-fold and this difference persisted for 72 h. These findings suggest that during the early phases of hepatic regeneration, because of decreased GST and GSH levels, the liver may be unusually susceptible to injury by toxic compounds. However, by the first round of cell division (36-48 h post-surgery) the liver has fully recovered its ability to metabolize toxic electrophiles.